(untitled) (TAJ: Journal of Teachers Association, 2019)
Intestinal Obstruction is a common surgical emergency and constitutes a major cause of morbidity and financial expenditure in hospitals around the world. This study aimed to provide the current spectrum of intestinal obstruction in a tertiary care hospital with a special view to identify any change in the aetiologic pattern. This prospective observational study was carried out in all four surgical units of Rajshahi Medical College Hospital from September 2010 to August 2011. The study included 250 adult patients with clinical and radiological evidence of complete intestinal obstruction. Out of 250 consecutive patients ranging between (13-90) years with a male to female ratio of 2.1:1, the maximum cases were within (31-40) years and (51-60) years of age group. In this study 175 cases (70%) were presented with small bowel and 75 cases (30%) with large bowel obstruction. The main causes of obstructions were bands and adhesions (44%) followed by volvulus (18%), external hernias (16%), neoplasm (12%), intussusceptions (3.2%), intestinal tuberculosis (2.8%) and miscellaneous (4%). Approximately, 86% patient with adhesive obstructions had previous laparotomy while 42% needed surgical exploration for failed conservative management. The overall mortality was 8%; mainly owing to strangulating obstruction and old age. Varying degrees of wound infections were the common post-operative complications. There was a significant change in the aetiologic pattern of intestinal obstruction. Post operative adhesions were the commonest cause of obstruction and appendicectomy was the most common previous operation causing adhesion. TAJ 2019; 32(1): 62-69